2001
DOI: 10.1111/j.1745-9125.2001.tb00934.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Deprivation and Changes in Homicide Arrest Rates for White and Black Youths, 1967–1998: A National Time‐series Analysis*

Abstract: Using time-series techniques with national data for 1967-98, we model the effects on changes in age-race-specific arrest rates of changes in indicators of economic deprivation. A measure of child poverty is positively related to juvenile arrest rates for both races, whereas changing unemployment (lagged) yields a surprising negative effect on youth offending. Measures of intraracial income inequality are also associated with changes in juvenile arrest rates, but the effects differ by race. Between-race inequal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 31 publications
0
35
0
1
Order By: Relevance
“…They argued that when people are unemployed they prefer to be at home and consume less on luxuries so they are less likely to be criminal. Similarly, Messner et al (2001) and Witt et al (1998) also found the negative significant effect of unemployment rate on crime rate in United States. However, in case of Australia, no evidence was found that unemployment rate causes the crime rate (Masih and Masih 1996;Narayan and Smyth 2004).…”
Section: Macroeconomic Determinants Of Crime Causationmentioning
confidence: 70%
“…They argued that when people are unemployed they prefer to be at home and consume less on luxuries so they are less likely to be criminal. Similarly, Messner et al (2001) and Witt et al (1998) also found the negative significant effect of unemployment rate on crime rate in United States. However, in case of Australia, no evidence was found that unemployment rate causes the crime rate (Masih and Masih 1996;Narayan and Smyth 2004).…”
Section: Macroeconomic Determinants Of Crime Causationmentioning
confidence: 70%
“…Still, official records from police and courts consistently show that lower class men and male youth are more involved in crime and delinquency than the middle class. Individuals in poor and minority neighborhoods are also likely to self-report crime at relatively high rates, regardless of their own social class (Braithwaite 1980 , 1967-1998, were also weakly related to income inequality and reliably related only to unemployment rates among whites but not blacks (Messner et al 2001). In sum, ecological studies of states and national time series have not consistently linked levels of offending to either incomes or employment in the period when low-skill men's economic opportunities deteriorated mostthrough the 1980s and 1990s.…”
Section: The Labor Market and Crimementioning
confidence: 99%
“…Given what we know from outside of Alaska about the effects of poverty, relative deprivation, and a lack of legitimate opportunities (Lauritsen Downloaded by [McMaster University] at 20:49 14 June 2016& White, 2001Messner, Raffalovich, & McMillan, 2001;Morenoff, Sampson, & Radenbush, 2001), it would be reasonable to examine the impact of those social forces upon crime in Alaska and upon the criminal justice system processing of those who are most likely to face such conditions.…”
Section: Resultsmentioning
confidence: 99%